Demolition of Province House on Washington Street, ca. 1922 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of Province Street, located on Washington Street at Province Street and Province Court. Construction equipment, debris and construction workers are included in the photograph. Province House, 1679-1922; former residence of the British Royal Governor 2 11/16 x 4 1/2 Photographs